INTERFERENSI BAHASA INDONESIA TERHADAP TULISAN BERBAHASA PRANCIS PADA MAHASISWA SASTRA PRANCIS UNIVERSITAS NEGERI SEMARANG - Nugroho, Lutfi Hadi (Universitas Hasanuddin, 2023)
There are quite a lot of Indonesian-speaking learners who study foreign languages in Indonesia, one of which is French Literature students of UNNESwho study French can be called B2 (second language) because the main language or first language learned, namely Indonesian called B1. This study used qualitative research methods. The purpose of this study was to describe the interference of Indonesian to writing about French-language semester holidays of French Literature Students of UNNES. Furthermore, this study used a sample of 6 student writings in the Production Écrite Élementaire coursework. Based on the results of the analysis that has been carried out, there were 41 interferences made by students of the class of 2021 French Literature FBS UNNES in writing about semester holidays in the Production Écrite Élementaire course. The details of the 41 interference errors are 22 grammatical interferences, 9 lexical inteferences, 10 orthographic interferences, and 0 phonological interferences.